IMPLEMENTATION OF INQUIRY APPROACH TO IMPROVE STUDENTS 'LEARNING MOTIVATION IN PKN LESSONS IN KELAS IX-1 SMP NEGERI 1 NAMORAMBE STUDY YEAR 2017/2018 - Latifah Hanum Tarigan (Universitas Dharmawangsa, 2020)
Motivation is a change in energy in a person that is characterized by the emergence of feelings and is preceded by a response to the existence of learning objectives, namely changes in behavior or appearance, with a series of activities such as reading, observing, listening, imitating This research aims to determine the increase in student learning motivation by using Inquiry approach in Class IX-1 SMP Negeri 1 Namorambe Academic Year 2017/2018. The research method is classroom action research and the research subject is Class IX-1. The class studied consisted of 34 students. Based on the learning outcomes of the first cycle, an average value of 70 was obtained. After the second cycle, there was an increase to 85. In this study, data on individual and classical learning completeness criteria were obtained, to as many as 34 students or by 100%. Thus the learning in this study can be said to have been completed. The level of student mastery of the material being taught, which is made based on the final test is 100% of students who have very high mastery. Based on the results of the research above, it can be concluded that learning using the inquiry approach in Class IX-1 SMP Negeri 1 Namorambe for the 2017/2018 academic year has increased student learning motivation.